2017
DOI: 10.1590/0103-6513.213616
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable procurement portfolio management: a case study in a mining company

Abstract: Sustainable procurement is a solution to integrate environmental and social considerations in all steps of procurement process, in order to reduce impacts on human health, environment, and human rights. Despite the existence of important works in this area, more studies for determining how the principles related to sustainable development can be integrated to procurement strategies are needed. This study presents a case study in a mining company to evaluate the elements that should be considered for the implem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…For selecting the suppliers to undergo GSD programs, the buyer company sorts out all its purchased items into the categories based on Portfolio Model (Olsen and Ellram, 1997; Mello et al , 2017) as shown in Figure 1. Strategic (high-profit impact, high supply risk), bottleneck (low-profit impact, high supply risk), leverage (high-profit impact, low supply risk), and noncritical (low-profit impact, low supply risk) (Kraljic, 1983).…”
Section: Literature Surveymentioning
confidence: 99%
“…For selecting the suppliers to undergo GSD programs, the buyer company sorts out all its purchased items into the categories based on Portfolio Model (Olsen and Ellram, 1997; Mello et al , 2017) as shown in Figure 1. Strategic (high-profit impact, high supply risk), bottleneck (low-profit impact, high supply risk), leverage (high-profit impact, low supply risk), and noncritical (low-profit impact, low supply risk) (Kraljic, 1983).…”
Section: Literature Surveymentioning
confidence: 99%
“…The current concept of sustainable development considers at least three key components: economic growth, environmental protection and social equality (Mello et al, 2017). The issue of sustainability in global supply chain management, as focused on these components, has drawn significant attention from various researchers.…”
Section: Sustainable Scmmentioning
confidence: 99%
“…In the last decades, more intensely since 1970, the greater international debate on the search for development models which reconcile economic growth, social justice, conservation and sustainable use of natural resources has resulted in several reports and conferences which have shown the tragic environmental situation in the planet (Mello et al, 2017;Siva et al, 2016).…”
Section: Introductionmentioning
confidence: 99%